Cluster decays of 12Be excited states - Vukman, Nikola; Soić, Neven; Freer, Martin; Alcorta, Martin; Connolly, Devin; Čolović, Petra; Davinson, Thomas; Di Pietro, Alessia; Lennarz, Annika; Psaltis, Athanasios; Ruiz, Chris; Uroić, Milivoj; et al. (Frontiers in Physics, 2022)
An experimental study of the helium-cluster decays of the ^12Be excited states has been performed using the ^9Li + ^7Li α + α + ^8He and ^9Li + ^7Li α + ^6He + ^6He reactions at the ^9Li beam energy of 74.8 MeV. At excitation energies between 10 to 25 MeV, the ^12Be excited states decaying into the ^4He + ^8He, ^6He + ^6He and ^6He + ^6He*(1.8 MeV, J^π = 2^+) have been observed. Most of the observed states decaying into the ^4He + ^8He and ^6He + ^6He correspond to previously reported states. The decay to the ^6He + ^6He*(1.8 MeV, J^π = 2^+) channel has been observed for the first time. Two of the five states observed in this new decay channel are also observed in the ground state channel ^6He + ^6He, while two may correspond to the ^4He + ^8He decaying states. The states around 13.5 and 20.0 MeV decay to the ^6He + ^6He and ^4He + ^8He channels, while the state around 22.3 MeV decays into all three decay channels examined. This experiment is complementary to all previous studies of the ^12Be cluster states because of the different reaction mechanism employed for the population of the ^12Be cluster states. The observation of the states at high excitations with these exotic decay properties is strongly supporting the molecular structure of the ^12Be excited states.